A note on the two-dimensional electrostatic field produced by a line charge near a dielectric wedge. Issue 3 (20th May 2019) - Rawlins, A D
Summary: We shall consider the problem of determining the correct electrostatic field produced when an infinite two-dimensional line source is influenced by an adjacent infinite dielectric wedge. This result corrects a number of previous attempts at this problem, which are shown to be in error. The method avoids using the Mellin transform which has lead to some of these earlier errors. The method is used to solve a more general problem of the electrostatic field produced by an arbitrary number of line sources located in an arbitrary number of contiguous dielectric wedges.